Thermodynamic simulation on thixoformability of aluminium alloys for semi-solid metal processing - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi; Mohammed, Mohamad Naser; Alhawari, Khalid Salim (North Atlantic University Union, 2013)
Semi-solid metal (SSM) processing is a relatively successful method for forming alloys in the semi-solid state to near net shaped products. One type of SSM processing is thixoforming which is used widely in the automotive industry to produce near netshaped parts. All the alloys that have been used to date for thixoforming were developed originally for either casting or forging purposes. Therefore, it is necessary to modify existing commercial alloys in order to improve the potential of these alloys for use in thixoforming. In the present work, thermodynamic simulations were utilised to determine the working window temperature, solidification temperature range and fraction liquid sensitivity of modified A319 commercial alloy. All the calculations in the present work are performed using JMatPro software. The conditions of the nonequilibrium solidification are determined using the Scheil-Gulliver equation. A key advantage of the JMatPro software is that it allows the calculation of the formation conditions for the various stoichiometric compounds (exp: α-Al(Fe,Mn)Si, β-AlFesi, Al5Cu2Mg8Si6, Al7Cu2M and Al2Cu), which has a great influence on the mechanical properties of aluminium alloys. The results indicate that these modified alloys are potential materials for thixoforming.